2012
DOI: 10.1124/dmd.112.045039
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of (2S)-Pterosin A: Identification of the Phase I and Phase II Metabolites in Rat Urine

Abstract: ABSTRACT:The metabolic profile of the potent hypoglycemic agent, (2S)-pterosin A (1), in rat urine via intragastrical oral administration was investigated. In total, 19 metabolites (M1-M19) were identified. Among these, 16 metabolites were characterized by high-performance liquid chromatography solid-phase extraction-tube transfer-NMR, and seven metabolites were further isolated from the treated urine to enable further structural determination. Twelve of these are new compounds. The phase I metabolites of 1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…However, another cyclic lactone pterosin, (S)-12-hydroxy-2-hydroxymethylpterosin E 14, 12-lactone, with one extra methylene has been reported as a metabolic product of (2S)-pterosin A in rat urine via oral administration (100 mg/kg) (Lee et al, 2012). Other metabolites of (2S)-pterosin A were compounds 14, 27 and 29, which we isolated for the first time from plant material.…”
Section: Structural Relationships Between New and Known Pterosins Andmentioning
confidence: 79%
See 2 more Smart Citations
“…However, another cyclic lactone pterosin, (S)-12-hydroxy-2-hydroxymethylpterosin E 14, 12-lactone, with one extra methylene has been reported as a metabolic product of (2S)-pterosin A in rat urine via oral administration (100 mg/kg) (Lee et al, 2012). Other metabolites of (2S)-pterosin A were compounds 14, 27 and 29, which we isolated for the first time from plant material.…”
Section: Structural Relationships Between New and Known Pterosins Andmentioning
confidence: 79%
“…One-and two-dimensional NMR experiments combined with mass spectrometry were used to identify thirteen novel natural products (1-13) (Supplementary Information 1) belonging to the sesquiterpenoid family. The structures of twenty two previously reported pterosins and pterosides 14, 27, 29 (Lee et al, 2012), 15-18, 30-33, 35 (Kuroyanagi et al, 1979), 19-25 (Fukuoka et al, 1978), 26 (Kuraishi et al, 1985;Tanaka et al, 1982), 28 (Murakami et al, 1980), 34 (Castillo et al, 2003) were determined by the comparison of their spectroscopic data with those reported in the literature . The structures of compound 1-13 are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological studies have demonstrated its effectiveness against inflammatory diseases such as hepatitis, gastritis, neuralgia, and appendagitis [1][2][3][4]. Although the major bioactive components in Sinisan crude drug, such as liquiritin (P2), albiflorin (11), paeoniflorin (13), naringin (23), neohesperidin (27), glycyrrhizin (49), saikosaponins a (50), and d (P7), have been studied [4][5][6], it is necessary to figure out the in vivo metabolic profile for characterizing the fate of active components and to elucidate the in vivo functions of the metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are stored in the root cells for subsequent This (root exudates) is the more probable means by which fern allelochemicals are released into the soil, which explains the higher inhibitory activity (both on germination and growth) of extracts, which also inhibited the root growth of P. pratensis. This probably indicates interferences between P. aquilinum allelochemicals and growth phytohormones [3]. For example, depending on the pH of the soil, ptaquiloside may decompose according to the following reaction scheme (Figure 4).…”
Section: Introductionmentioning
confidence: 99%